Model Pendidikan Karakter Untuk Anak Usia Dini Perspektif Qs. Luqman Ayat 12-19 - Rizqiyah Ratu Balqis (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Basically, the values of education contained in the QS Luqman verses 12-19, are the values of character education, including: monotheism, gratitude, patience, amar ma`ruf nahi mungkar, religious education, and honesty. The wise character (wisdom) is found in Luqman's educational interaction model with his child and between his family. The dominance of this wise nature underpins the interaction of education carried out to his children. The wise attitude of Luqman is directed at the effort to form characters (children) into human beings, that is, having good character and virtuous characterKeyword : Model, Pendidikan Karakter, QS Luqman ayat 12-19